2015
DOI: 10.1002/hbm.22868
|View full text |Cite
|
Sign up to set email alerts
|

Emotional context facilitates cortical prediction error responses

Abstract: In the predictive coding framework, mismatch negativity (MMN) is regarded a correlate of the prediction error that occurs when top-down predictions conflict with bottom-up sensory inputs. Expression-related MMN is a relatively novel construct thought to reflect a prediction error specific to emotional processing, which, however, has not yet been tested directly. Our paradigm includes both neutral and emotional deviants, thereby allowing for investigating whether expression-related MMN is emotion-specific or un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 66 publications
2
35
0
2
Order By: Relevance
“…the 71 effect of expectation on conscious perception is exaggerated for emotional stimuli. Previous studies have found 72 that surprise-related evoked potentials are larger and earlier for emotional than neutral stimuli (Vogel et al, 2015, 73 Kovarski et al, 2017, Chen et al, 2017. If the effect of expectation is even larger for emotional stimuli, as this 74 suggests, then we might expect that earlier conscious perception of expected than unexpected stimuli (after an 75 initial period of unawareness) is even more extreme for emotional stimuli.…”
Section: Introduction 28mentioning
confidence: 81%
“…the 71 effect of expectation on conscious perception is exaggerated for emotional stimuli. Previous studies have found 72 that surprise-related evoked potentials are larger and earlier for emotional than neutral stimuli (Vogel et al, 2015, 73 Kovarski et al, 2017, Chen et al, 2017. If the effect of expectation is even larger for emotional stimuli, as this 74 suggests, then we might expect that earlier conscious perception of expected than unexpected stimuli (after an 75 initial period of unawareness) is even more extreme for emotional stimuli.…”
Section: Introduction 28mentioning
confidence: 81%
“…Here, the shorter vMMN latency to the oblique bar pattern (a simple stimulus) indicates that deviancy is detected earlier in the context of complex stimuli than a complex deviant event within the sequence of more simple ones. When the standard and the deviant are similar [e.g., belonging to the same category (oblique lines: Kimura et al ( 2009 , 2010 ); facial categories and emotions: Yu et al ( 2017 ), Vogel et al ( 2015 ), Kreegipuu et al ( 2013 ); left vs. right hand: Stefanics and Czigler ( 2012 )], deviant-related negativity included longer latency ranges, or there were mismatch components in various ranges, whereas in the case of highly different standard and deviant (e.g., symmetric vs. asymmetric patterns), the difference potential was confined to an earlier and narrower latency range. Furthermore, using similar standards and deviants such as disappearing parts of an object (Sulykos et al 2017 ) and checkerboards with alternating locations of the dark and light squares (Sulykos et al 2018 ), an identical earlier phase of the vMMN appeared for both younger and older groups, whereas the later part was absent or diminished in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…According to this model, vMMN is elicited when an input does not match the prediction induced by regular and probabilistic representation. This interpretation would explain not only deviancy effects in oddball paradigms, but also violations of regularity in sequential patterns (see Kimura et al, 2011 ; Kimura, 2012 ; Vogel et al, 2015 ).…”
Section: Introductionmentioning
confidence: 98%